Topological Spin Excitations in Honeycomb Ferromagnet CrI_{3} - Lebing Chen; Jae-Ho Chung; Bin Gao; Tong Chen; Matthew B. Stone; Alexander I. Kolesnikov; Qingzhen Huang; Pengcheng Dai (Physical Review X, 2018)
In two-dimensional honeycomb ferromagnets, bosonic magnon quasiparticles (spin waves) may either behave as massless Dirac fermions or form topologically protected edge states. The key ingredient defining their nature is the next-nearest-neighbor Dzyaloshinskii-Moriya interaction that breaks the inversion symmetry of the lattice and discriminates chirality of the associated spin-wave excitations. Using inelastic neutron scattering, we find that spin waves of the insulating honeycomb ferromagnet CrI_{3} (T_{C}=61  K) have two distinctive bands of ferromagnetic excitations separated by a ∼4  meV gap at the Dirac points. These results can only be understood by considering a Heisenberg Hamiltonian with Dzyaloshinskii-Moriya interaction, thus providing experimental evidence that spin waves in CrI_{3} can have robust topological properties potentially useful for dissipationless spintronic applications.